Faktor Tingkat Pendidikan, Usia, Paritas, Status Pekerjaan dan Riwayat Emesis Gravidarum Mempengaruhi Terjadinya Emesis Gravidarum Pada Ibu Hamil Trimester I - Munisah Munisah; Rahmawati Ika Sukarsih; Aidha Rachmawati; Siti Mudlikah (Universitas Muhammadiyah Gresik, 2022)
Nausea and vomiting is one of the signs and symptoms of pregnancy that commonly occurs in pregnant women in the early first trimester of pregnancy. Nausea and vomiting are also known as emesis gravidarum. If emesis gravidarum is not handled properly, it can become a pathological condition that can affect the health of the mother and fetus. The purpose of this study was to determine the effect of the factors that influence the emission of gravidarum. This study used a descriptive analytic correlation design using a cross sectional research design. This research was conducted from December 2021 to February 2022 at the Independent Midwife Practice (PMB) Suhartini Tulangan Sidoarjo. The research subjects were 50 people who were pregnant women in the 1st trimester and experienced emissions of gravidarum. Statistical test using correlation test using the product moment formula. The results showed that the education level factor t count = 1.631, age t count = 0.411, parity t count = 1.01, employment status t count = 0.242 and history of emissions gravidarum t count = 0.101. While the t table value of the five factors above of 2.064, so the value of t count is smaller than t table, then Ho is accepted. Conclusion: there is no influence between education level, age, parity, employment status and history of gravidarum emissions with the incidence of gravidarum emissions experienced by pregnant women.